(untitled) (GYMNASIUM, 2017)
Body scheme plays a crucial role in child development. This influences both the growth and the development of the individual. If the scheme is properly integrated body, the individual will develop harmoniously, but if there are disturbances of body schema, it can interfere with the growth and development of the child. Body scheme is an element underpinning the construction of individual personality, is vital to this process and enhancing self-esteem. Investigative approach comes to prove the correlation between body scheme in line with the maturing child. The previous statement is the premise of research and will be verified by two tests. Call and send test results relevant to the objective of the research: a well-defined scheme favors body location in space, the execution of daily actions and relationships with people around you.